Ultrasonographic Assessment of Uterine Measurements and Endometrial Thickness Among Healthy Saudi Females Sample - Hassan MG; Alnafa HM; Alsofyan N; Alsulimi RS; Alsllal S; Abaalkhail NA; Alzurayr M; Alamr H; Elmahdi TS; Aldahes AS; Wanasi M; Hawesa H (International Journal of Women's Health)
Mahasin G Hassan,1 Huda M Alnafa,1 Norah Alsofyan,1 Reham S Alsulimi,1 Sumayah Alsllal,1 Noura A Abaalkhail,1 Mona Alzurayr,1 Hessah Alamr,1 Tasneem SA Elmahdi,2 Asma S Aldahes,1 Mayson Wanasi,3 Halima Hawesa1 1Department of Radiological Sciences, College of Health and Rehabilitation Sciences, Princess Nourah bint Abdulrahman University, Riyadh, Saudi Arabia; 2Department of Diagnostic Radiologic Technology, Faculty of Applied Medical Sciences, Taibah University, Al-Madinah Al-Munawara, Saudi Arabia; 3Department of Radiological Sciences, Al-Ghad International Colleges for Applied Sciences, Madina, Saudi ArabiaCorrespondence: Mahasin G Hassan, Department of Radiological Sciences, College of Health and Rehabilitation Sciences, Princess Nourah bint Abdulrahman University, PO Box 84428, Riyadh, 11472, Saudi Arabia, Tel +966553661276, Email mghassan@pnu.edu.saAim: The present study was conducted to analyze uterine measurements and endometrial thickness throughout the menstrual cycle in Saudi healthy females of reproductive age.Methods: This cohort study was conducted at Princess Nourah bint Abdulrahman University, Saudi Arabia, among thirty-three females of reproductive age who underwent trans-abdominal pelvic ultrasound scans across four menstrual cycle phases. Data analysis was conducted using SPSS version 26, utilizing descriptive statistics, one-way ANOVA, correlation, and regression analysis.Results: Endometrial thickness and layers showed significant variations (p< 0.001) across menstrual phases (early proliferative: 0.59 ± 0.21 cm, late proliferative: 0.77 ± 0.24 cm, secretory: 1.09 ± 0.40 cm, menstrual: 0.52 ± 0.35 cm). Endometrial thickness was positively correlated with number of layers (r=0.576, p< 0.05). The study showed that the average uterine length, width, and thickness were 7.33 ± 0.76 cm, 3.93 ± 1.00 cm and 3.44 ± 0.55 cm, which showed stability across menstrual phases, except for width showing slight variations. Endometrial thickness was positively correlated with uterine thickness (r=0.358, p< 0.05).Conclusion: The study results emphasize the significance of using region-specific reference values in clinical practice. This approach would enable precise evaluation and treatment of gynecological problems. It is encouraged to do future study with larger populations in order to validate these results and improve the therapeutic applicability.Keywords: endometrial thickness, endometrial layering, ultrasound, uterus, menstrual phase